An overview of critical chain applied to project management - Correia, Francisco (2011)
The characterization and assessment of the Critical Chain (CC) approach and the adaptation of the Theory of Constraints (TOC) to Project Management is an important element to help promoting the development of this field. Starting with a brief discussion about the CPM method and PERT method, this paper introduces some discussion about the advantages and disadvantages of the CC concerning to traditional approaches.